Last row, third from the left Dick van Galen Last. Van Galen Last participated in an international protest march in solidarity with conscientious objectors in Spanish prisons
Last row, third from the left Dick van Galen Last. Van Galen Last participated in an international protest march in solidarity with conscientious objectors in Spanish prisons.